Reconceptualizing the Concept of Corporate Governance and its Goals in People’s Credit Banks in Indonesia - Yafet Yosafet Wilben Rissy (Yuridika, 2021)
This Article examines the concept of corporate governance and its goals in People’s Credit Banks (PCBs). In 2015, Indonesian Financial Services Authority (IFSA) issued two main regulations on corporate governance and risk management for People’s Credit Banks (PCBs). This investigation shows that in these two regulations ISFA simply defines corporate governance as the implementation of transparency, accountability, responsibility, independence and fairness (TARIF) principles by PCBs. Basically, such kind of conceptualization is not appropriate as it does not define the concept of corporate governance itself, but rather, it just reaffirms the general principles of good corporate governance. Meanwhile, IFSA does not clearly provide the goals of corporate governance in PCBs. It is recommended that IFSA should reconceptualize the definition of corporate governance by focusing more on the function of PBCs boards. Meanwhile, the goals of corporate governance in PCBs should deal more with the achievement of long-term success of PCBs.